Sexual health knowledge, attitudes and behaviours of Filipino college students - Dy, Marison R.; Dy, Erick Vernon Y. (2014)
The study aimed to determine the socio-demographic characteristics of selected college students; their sexual knowledge levels, attitudes and behaviours; their sources of influence in relation to sexual knowledge, attitudes and behaviours; and the socio-economic and demographic correlates of their sexual knowledge, attitudes and behavioural intentions. The findings demonstrate that these selected Filipino college students have high levels of sexual knowledge (83%) but have gaps in relation to withdrawal, rhythm method and fertilization. Their sexual attitudes favor the delay of sexual intercourse and non-usage of contraceptive devices. The intention to engage in premarital sex was low. An average of 25% of the respondents have engaged in premarital sex during their mid-to late adolescent years. The people considered as helpful in preventing premarital sex are the priest/religion, parents, the girlfriend and the siblings. Sexual knowledge was correlated with age of respondents and parental educational attainment. A conservative sexual attitude was correlated with maternal educational attainment. Low intention to engage in premarital sex was correlated with living away from the parents. Lastly, sexual attitude and intention to engage in sex were correlated. To ensure adolescent sexual health, effective sexuality education programs with parental involvement and education must be designed and implemented.
Keywords: Sexual behavior